Multi-fixed smeared 3d crack model to simulate the behavior of fiber reinforced concrete structures - Gouveia, A. Ventura (2008)
When a concrete structure is subjected to a multi-stress state, different crack modes can be developed. To simulate with enough accuracy these fracture modes, a three dimensional model must be used. In the present work, a multi fixed smeared 3D crack model is proposed to predict the normal and shear failure modes of concrete structures. Softening stress strain diagrams are proposed to model, after crack initiation, the normal and shear components. The performance of the developed model was appraised by simulating the behavior observed in punching tests with lightweight panels of steel fiber reinforced self compacting concrete (SFRSCC).